How can everyday practical knowledge be understood with inspiration from philosophy? - Lykkeslet, Else (Nursing philosophy, 2006)
Many nursing scholars are inspired by philosophy when investigating phenomena within nursing. This paper focuses on the everyday practical knowledge of nurses. Based on an empirical project carried out in a surgical ward the authors make an attempt, with help from philosophy, at identifying and conceptualizing elements of knowledge in everyday practice. With reference to texts by Heidegger and Wittgenstein the authors investigate two dimensions of nursing knowledge: a dimension of doing and a dimension of being. These dimensions are further developed and concretized in the paper. The doing dimension is emphasized through the concepts of adapting and exploring. The being dimension has its basis in being understanding and being connected. These two dimensions constitute a form of knowledge which is mobile and flexible. This knowledge is in place in everyday situations and it works where it is supposed to work.